Vitamin D endocrine system: mechanisms to produce biological responses - Norman, Anthony (Henry Stewart Talks, 2007)
Optimal ligand shapes, Modes of action of hormone-D, Shape of ligand for VDRNUC, Three dimensional shape of the VDR, Shape of ligand for DBP, DBP structure domains A, B, C, Shape of ligand for rapid responses, Steroid receptor superfamily, Steroid receptor domains, Structural organization of VDR gene, mRNA and protein, Model of steroid hormone mode of action, Model of hormone-D transcriptional activation, Determination of a VDR mediated genomic response, Examples of rapid responses, Caveolae membrane and rapid responses, VDR knock out mouse and rapid responses